The Influence of Financial Literacy and Financial Behavior of FEB UNJ Students on Crypto Investment Decisions - Nanda Melandri; Afidah Nur Aslamah; Osly Usman; Ryna Parlyna (Journal of Strategic Marketing and Innovation, 2025)
Objective: This study seeks to examine the effects of Financial Literacy and Financial Behavior on Crypto Investment Decisions in students UNJ Faculty of Economics and Business (FEB), with Investment Motivation as the mediator. Based on the quantitative method, a total of 102 received for this study and analyzed by using SEM-PLS. The results indicate that Financial Literacy and Financial Behavior have a positive and significant influence on Investment Motivation, in turn, it influences Investment Decisions. Crucially, mediation analysis demonstrates that Investment Motivation mediates the path from Financial Literacy to decisions but fails to mediate Financial Behavior. Instead, Financial Behavior exerts a strong direct influence on decisions. It is concluded that while knowledge requires a motivational bridge to translate into action, financial discipline acts as a direct enabler. These findings imply that financial education should integrate rational motivational strategies with practical habit formation to mitigate investment risks.